PERAN TEKNOLOGI DALAM IMPLEMENTASI STRATEGI MANUFAKTUR PADA PERUSAHAAN MANUFAKTUR DI INDONESIA: STUDI DENGAN PENDEKATAN KONTINGENSI - Lina Anatan (KINERJA, 2006)
Expanding global competition, rapidly changing market and technology, increasingcomplexity and uncertainty are creating a new competitive environment. To be successful in this globally competitive and rapidly changing environment, organization must formulate strategic plan that is consistent with their investment and technology. This research was conducted to investigate the relationship among manufacturing strategy, technology adoption, and firm performance. Data were collected through mailed questionnaires (525 questionnaires) and direct survey in 25 firms. The questionnaires were sent to 550 CEOs of manufacturing firm in Indonesia. A hundred and six responses returned and made a response rate of 19.27%. The study finds different results for hard and soft technology. Hard technology moderates the relationship between manufacturing strategy and operational performance, as a quasi moderator variable. On the other hand, soft technology has an impact on the manufacturing strategy-performance relationship as an independent predictor variable, but it does not moderate the relationship between manufacturing strategy and operational performance.Keywords: manufacturing strategy, technology adoption, operational performance, technology